Major branches and elements of robotics [ - Larose, Leilani (New York : University Publications, 2014)
This book is a complete package for knowledge sharing on major branches and elements of robotics
1. BEAM robotics -- 2. Nanorobotics -- 3. Robot kinematics -- 4. Computer vision and machine vision -- 5. Electronic stability control -- 6. Speech processing -- 7. Other important branches of robotics
Keywords: Nanoelectromechanical systems; Robotics